Food rescue as collective care. Issue 1 (24th November 2021) - Diprose, Gradon; Lee, Louise
Abstract: Recent research into waste has moved beyond focusing on individual behaviour change to the wider practices, systems, and social norms that construct and perpetuate waste. Running alongside this work on waste, community economy scholars have been exploring how communities form around and care for commons. In this paper we draw on social practice theory and community economy thinking to illustrate how a food rescue organisation, Kaibosh, based in Wellington, New Zealand, has created practices and mobilised meanings that enable people to collectively manage surplus food, address food poverty, and reduce waste. We show how these food rescue and distribution practices push back against individualised despair, moralism, or guilt, and connect people across food systems. Recent critiques of food rescue and wider food philanthropy argue that such practices can be used to justify further welfare retreat, or distract from the need for genuine agri‐food sector reform. While we are sympathetic to these critiques, our findings suggest something different: people get involved in food rescue as a practical way to address food injustice and waste. We show how social practice theory can be used to understand how communities form around a commons that responds to pressing socio‐environmental issues in the here and now. Abstract : Recent research into waste has moved beyond focusing on individual behaviour change to the wider practices, systems, and social norms that construct and perpetuate waste. Running alongside this work on waste, community economy scholars have been exploring how communities form around and care for commons. In this paper we draw on social practice theory and community economy thinking to illustrate how a food rescue organisation, Kaibosh, based in Wellington, New Zealand, has created practices and mobilised meanings that enable people to collectively manage surplus food, address food poverty, and reduce waste.